23 - EVOLUTION OF ANTHROPOMETRIC AND FUNCTIONAL VARIABLES IN UNIVERSITY STUDENTS; (Fiep Bulletin - online, 2022)
Introduction: The transition from high school to college entails changes in students' habits, which modify the body composition and functionality of the students. Objective: To identify and analyze anthropometric and functional changes in weight, height, body mass index (BMI) and flexibility, as well as abdominal and upper limb strength in university students through different semesters. Material and methods: The study was designed to carry out evaluations in three different moments: first, second and third semester of university, 26 students participated in the first semester, and 16 in the second and third semesters. The anthropometric variables of body weight, height and BMI were determined, and selected variables of abdominal strength, upper limbs and flexibility were also evaluated. Results: The anthropometric variables in men only found a significant difference in age between First vs. Fifth (p=0.01), however, an increase in weight and BMI was observed. In females no significant difference was found in anthropometric variables, however, an increase in weight, and BMI was observed comparing Second vs. Fifth. Conclusions:The students evaluated belong to a degree program whose graduation profile includes the study of the problem of overweight-obesity and have at least one subject that requires them to engage in physical activity; therefore, the data show normal values for BMI as well as a good capacity in the functional tests in both strength and flexibility.